2020
DOI: 10.3390/su12229700
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Six Genotypes of Tritordeum Compare to Bread Wheat under East Mediterranean Condition

Abstract: Four advanced tritordeum lines were studied and compared to two commercial varieties of tritordeum and wheat cultivars in yield and quality features, in Greece. For this purpose, a two-year experiment was established in the Greek territory. The field experiment was set up in Randomized Complete Block Design (RCBD) with blocks, with different lines and varieties. Head emergence was calculated based on Growing Degree Days (GDDs), which was significantly affected by the year. The significance of differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Contrariwise to our results, Kakabouki et al (2020) was observed that relative production efficiency and had grain specific weight had a negative correlation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Contrariwise to our results, Kakabouki et al (2020) was observed that relative production efficiency and had grain specific weight had a negative correlation.…”
Section: Discussionsupporting
confidence: 88%
“…This indicator compares crops and production systems and is mostly affected by yields. Besides, in case of experimental varieties and lines, RPE gives information on the potential profits (Kakabouki et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has a lower grain yield [17]. However, it is important to note that new advanced lines of tritordeum outperform 'Aucan' and 'Bulel' for yield performance [18]. Table 1 summarizes the agronomic performance data available for tritordeum over time.…”
Section: Progress In Breeding For Agronomic Performancementioning
confidence: 99%
“…1 JB1 and JB3 were pre-selections of 'Aucan' and 'Bulel' registered varieties. 2 Two seasons (denoted as 1st and 2nd) were considered by [18]. 3 Relative performance compared to bread wheat control with the exception of First HTs that are compared to durum wheat parents.…”
Section: Progress In Breeding For Agronomic Performancementioning
confidence: 99%
“…A few recent studies in Europe have been focused on the agronomical traits, looking at yield performance of tritordeum cultivars (cvs) over conventional soft and durum wheats [7,12,13]. Scientific works have so far mainly focused on the bioactive compounds' content: tritordeum, in fact, has higher levels of carotenoids and arabinoxylans than wheat, and these result in a greater total antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%